Ice sheet collapse following a prolonged period of stable sea level during the last interglacial - O'Leary, Michael; Hearty, P.; Thompson, W.; Raymo, M.; Mitrovica, J.; Webster, J. (Nature Publishing Group, Macmillan Publishers Ltd, 2013)
During the last interglacial period, 127-116 kyr ago, global mean sea level reached a peak of 5-9m above present-day sea level. However, the exact timing and magnitude of ice sheet collapse that contributed to the sea-level highstand is unclear. Here we explore this timing using stratigraphic and geomorphic mapping and uranium-series geochronology of fossil coral reefs and geophysical modelling of sea-level records from Western Australia. We show that between 127 and 119 kyr ago, eustatic sea level remained relatively stable at about 3-4 m above present sea level. However, stratigraphically younger fossil corals with U-series ages of 118.1±1.4 kyr are observed at elevations of up to 9.5 m above present mean sea level. Accounting for glacial isostatic adjustment and localized tectonics, we conclude that eustatic sea level rose to about 9 m above present at the end of the last interglacial. We suggest that in the last few thousand years of the interglacial, a critical ice sheet stability threshold was crossed, resulting in the catastrophic collapse of polar ice sheets and substantial sea-level rise.